2011
DOI: 10.1007/s11426-011-4351-6
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of fluorescent hydroxyls-coated carbon dots with hydrothermal reaction and its application to optical sensing of metal ions

Abstract: Carbon dots (CDs) with average diameter of 3.1 ± 0.5 nm were facilely synthesized with candle soot through hydrothermal reaction in sodium hydroxide aqueous solution. The as-prepared CDs were covered with a lot of hydroxyls, possessed properties of good water-solubility, anti-photobleaching, salt tolerance, and low cytotoxicity, and had a fluorescence quantum yield (QY) of about 5.5%. The fluorescence of the hydroxyls-coated CDs could be selectively quenched by metal ions such as Cr 3+ , Al 3+ and Fe 3+ , whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(71 citation statements)
references
References 47 publications
2
68
0
1
Order By: Relevance
“…The peaks at 1584 cm −1 and 1090 cm −1 indicated the existence of C=C and C-O, respectively. While the peak centered at 2948 cm −1 was ascribed to the stretching vibrations of C-H [38]. It is found that the as-prepared CDs are surrounded by -OH groups which make the obtained CDs not only display excellent water solubility but also easily coordinate with some metal ions [39].…”
Section: Characterization and Fluorescence Of The Cdsmentioning
confidence: 94%
“…The peaks at 1584 cm −1 and 1090 cm −1 indicated the existence of C=C and C-O, respectively. While the peak centered at 2948 cm −1 was ascribed to the stretching vibrations of C-H [38]. It is found that the as-prepared CDs are surrounded by -OH groups which make the obtained CDs not only display excellent water solubility but also easily coordinate with some metal ions [39].…”
Section: Characterization and Fluorescence Of The Cdsmentioning
confidence: 94%
“…5). This could lead to the deprotonation at the surface of the CNPs and can subsequently weaken the intermolecular hydrogen bonds that initially attracting the CNPs together [33]. Aggregation often causes self-quenching to take place and will turn off the fluorescence.…”
Section: Sensing Potential Of Heavy Metal Ionsmentioning
confidence: 99%
“…It is reported that the optical, physical and chemical properties of produced CNPs are influenced by the molecular precursors used, methodology and the pre-treatment performed. Apart from optical sensing CNPs have found widespread applications in the areas of bioimaging [18,19], photocatalysis [20], optoelectronics [21], etc.…”
Section: Introductionmentioning
confidence: 99%